Implementasi Metode Load Balancing Sebagai Upaya Meningkatkan Kinerja Server - Rini Nuraini (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The use of the internet turns out to cause problems that must be found a solution. One of them is the service provider's server load which continues to increase. This condition is triggered by the increasing number of clients from time to time. Some sites even reported receiving hundreds of thousands of connection requests simultaneously from a number of clients. From these problems, research is needed that focuses on how to design and build a server system that is able to handle the increase in incoming requests so that the server load can be unraveled. The purpose of this research is that the service provider's server can improve its service to the client. There are several approaches to overcome these problems, one of which is by applying the load balancing method. So that by implementing load balancing, the incoming large load will be distributed to each of the service provider's servers. In the tests that have been carried out, the scalability of the system has increased. This is proven when a system with load balancing is given 10000 connections, the test results have an average response time of 44.42 ms. As for the system without load balancing, the test results have an average response time value of 185.88 ms. From the test results, it can be seen that the average response time of the server system with load balancing is smaller than without load balancing, so the service performance of the system can be continuously improved by implementing load balancing.